Origin and occurrence of clay minerals in the Ariyalur Group of sedimentary rocks, Cauvery basin, Tamil Nadu, India (Journal of Nepal Geological Society, 1999)
Clay mineral assemblages in the Ariyalur Group of sedimentary rocks were studied by X-ray diffraction analysis. The results of the study indicate that illite and smectite are the predominant clay minerals whereas kaolinite and chlorite occur in minor amounts. The Campanian-Lower Maastrichtian rocks (i.e., Sillakkudi and Kallankurichchi Formations) contain a large amount of illite. The study reveals that these sediments were derived from the continental erosion of pre-existing rocks that were subjected to low intensity chemical weathering associated with a temperate climate. A significant decrease in illite content is observed in the Ottakkovil Formation. It implies a climatic transition (from temperate to warm) during the Middle Maastrichtian time. On the other hand, a high content of pedogenic smectite in the Kallamedu Formation is indicative of warm climatic conditions with alternating dry and wet periods during the formation of this mineral.